2006
DOI: 10.1212/01.wnl.0000204230.16619.d9
|View full text |Cite
|
Sign up to set email alerts
|

The association of CAG repeat length with clinical progression in Huntington disease

Abstract: CAG repeat length has a small effect on rate of progression that may be clinically important over time. Individuals with the shortest expansions appear to have the best prognosis. These effects of the CAG length may be relevant in the analysis of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
79
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 30 publications
16
79
1
3
Order By: Relevance
“…7 In the present studies, we show that 3B5H10 reacts in situ with Htt exon-1 76Q, the PGQ 9 ␤-turn former, and the ␤-strand-alternating PGQ 6/12 protein. 3B5H10 reactivity was slightly higher for the PGQ 6/12 protein than for PGQ 9 ␤-turn former.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…7 In the present studies, we show that 3B5H10 reacts in situ with Htt exon-1 76Q, the PGQ 9 ␤-turn former, and the ␤-strand-alternating PGQ 6/12 protein. 3B5H10 reactivity was slightly higher for the PGQ 6/12 protein than for PGQ 9 ␤-turn former.…”
Section: Discussionsupporting
confidence: 56%
“…Normal length polyQ regions vary between 10 and 25 residues, while longer repeats of 36 glutamines or more can cause HD (6). Clinical studies in HD patients have shown that a longer repeat results in an earlier age of onset and a more rapid disease progression (7,8). Based on more recent work, Htt is thought to undergo several proteolytic cleavage events, resulting in a number of Htt truncation products (9,10).…”
mentioning
confidence: 99%
“…Another aspect that should be highlighted is that longer CAG repeat length may have a small effect on rate of disease progression 22 , so one should expect a slightly less favorable outcome among our patients with non-choreic movement disorders as their motor presentation of HD. Unfortunately, our study had the limitation of not having a longitudinal design and this hypothesis cannot be inferred at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals affected with HD have a polyQ region of 36 or more glutamine residues (4), and clinical studies have shown an inverse correlation between polyQ length and age of disease onset (5,6). Recent work indicates that Htt may undergo proteolysis, generating several truncation products (7,8).…”
mentioning
confidence: 99%